Investigación de escenarios de inversión para el óptimo mantenimiento de la red vial estratégica principal de las carreteras de asfalto, lastre y tierra correspondiente a los cantones El Guabo, Pasaje, Machala, Arenillas, Huaquillas y Santa Rosa de la provincia de El Oro. - Toro Ruiz, Herman Paholo (2015)
Whether all types of pavement deteriorates over time, whether it is by weather conditions such as rainfall and temperature changes or loads produced by vehicular traffic, also it depends on the type of structure either this by the materials and the type of design. The main objective of this research is to develop a strategic plan for the conservation and road maintenance investment scenarios for optimal maintenance of the main strategic road network of asphalt roads, ballast and corresponding to the cantons El Guabo, Pasaje, Machala earth, Arenillas Huaquillas and Santa Rosa De La Provincia De El Oro, for the next 20 years. The methodology used for this research was through internet sources, literature, interviews with staff of the autonomous provincial government of El Oro, finally linear programming for the analysis of investment scenarios. First the road network data to assess the status of current service, first stage with the budget of $ 10,500,000 from the provincial government's current condition to 95 points over three years is maximized and at the end of 20 years with 100 points was collected, with a budget of $ 681,605.85; the second I minimize a given cost with 70 points and 75 asphalt ballast condition, with a budget of $ 263,355.73 to take a road network in good condition, and the third we reduce greenhouse gas emissions to minimize the environmental impact with the same condition second stage.